Digital Marketing in Forming Preferences and Decisions to Purchase Local Skincare among Generation Z Women in Bandung City - Nazwa Sabila; Thalita Putri Jaelani; Nandini Aquila Lukito; Happy Paramita (International Journal Administration, Business & Organization, 2026)
This study examines how digital marketing elements, namely visual content, electronic word-of-mouth (eWOM), and narrative advertising, influence brand preference and purchase decisions among Generation Z women in Bandung. A quantitative explanatory survey was employed, collecting data via online questionnaire from 204 respondents selected through purposive sampling, and the data was analyzed using a method called Partial Least Squares Structural Equation Modeling (PLS-SEM) through measurement and structural model evaluation. The findings reveal that visual content exerts a positive and significant effect on brand preference, whereas eWOM shows a negative and significant effect, suggesting excessive exposure to unverified reviews paradoxically diminishes consumer preference, and narrative advertising shows no statistically significant effect. Furthermore, brand preference positively and significantly influences purchase decisions, confirming its role as a critical mediating variable. These findings indicate that the effectiveness of digital marketing elements depends on how stimuli are cognitively and affectively processed, making visual content quality and proactive eWOM management key priorities for marketers targeting Generation Z local skincare consumers. This study contributes to the S-O-R literature by integrating multiple digital marketing stimuli into a single explanatory model within the context of Indonesia’s local skincare industry.